Sejarah Perkembangan dan Pertumbuhan Hadis dari Masa Nabi Hingga Terbukukannya Kitab Hadis - Basri B; Abustani Ilyas; Muhammad Yahya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Hadith, as the second primary source of Islamic teachings after the Qur’an, has a long and complex history of development. This study examines the historical journey of Hadith from the time of the Prophet Muhammad (peace be upon him) until the formal compilation of Hadith books. This process includes three important phases: the era of the Prophet and his Companions, characterized by memorization and oral transmission; the era of the Tabi‘in, marked by early efforts of collection and verification; and the period of formal codification, which began in the second century of the Hijri calendar. This research employs a library research method with a historical-descriptive approach to analyze the dynamics of Hadith development. The findings indicate that the development of Hadith was influenced by various internal and external factors, including concerns over the fabrication of Hadith, the need for documentation, and the expansion of Islamic territories. The codification process involved rigorous methodologies, particularly the system of isnad (chain of transmission) and Hadith criticism, which remain the foundation of Hadith scholarship to this day. The conclusion of this study emphasizes that the compilation of Hadith was the result of a gradual process involving contributions from multiple generations of scholars while consistently maintaining the authenticity and accuracy of the transmission of the teachings of the Prophet Muhammad (peace be upon him).